Upaya Peningkatan Kualitas Pembelajaran Aqidah Akhlak Melalui Pemanfaatan Buku Cetak pada Siswa Kelas II Madrasah Ibtidaiyah Darud Da’wah Wal Irsyad Mareto Kecamatan Tanete Rilau Kabupaten Barru - Zakaria, Zakaria; Irwan, Irwan; B, Burhanuddin; Alam, Nur (AIJER: Algazali International Journal Of Educational Research, 2025)
This study aims to improve the quality of faith and Morals learning through the use of learning resources for second-grade students at Madrasah Ibtidaiyah DDI Mareto, Tanete Rilau District, Barru Regency. This research is a qualitative study. Data collection was conducted using observation, interviews, and documentation methods. The data was then analyzed using descriptive analytical techniques. Data validity was examined using data triangulation, which involved comparing the observation data with the interview data and documentation results. The results are as follows: (1) How is the learning process of students through the use of printed books on faith and morals among second- grade students at Madrasah Ibtidaiyah DDI Mareto in Tanete Rilau District, Barru Regency? (2) The development of improvements in the quality of Aqidah Akhlak learning through the use of printed books among second-grade students at Madrasah Ibtidaiyah DDI Mareto, Tanete Rilau District, Barru Regency.